Chloride intracellular channel proteins respond to heat stress in Caenorhabditis elegans. - Jun Liang; Yakov Shaulov; Cathy Savage-Dunn; Stephane Boissinot; Tasmia Hoque (PLoS ONE)
Chloride intracellular channel proteins (CLICs) are multi-functional proteins that are expressed in various cell types and differ in their subcellular location. Two CLIC homologs, EXL-1 (excretory canal abnormal like-1) and EXC-4 (excretory canal abnormal- 4), are encoded in the Caenorhabditis elegans genome, providing an excellent model to study the functional diversification of CLIC proteins. EXC-4 functions in excretory canal formation during normal animal development. However, to date, the physiological function of EXL-1 remains largely unknown. In this study, we demonstrate that EXL-1 responds specifically to heat stress and translocates from the cytoplasm to the nucleus in intestinal cells and body wall muscle cells under heat shock. In contrast, we do not observe EXC-4 nuclear translocation under heat shock. Full protein sequence analysis shows that EXL-1 bears a non-classic nuclear localization signal (NLS) that EXC-4 is lacking. All mammalian CLIC members have a nuclear localization signal, with the exception of CLIC3. Our phylogenetic analysis of the CLIC gene families across various animal species demonstrates that the duplication of CLICs in protostomes and deuterostomes occurred independently and that the NLS was subsequently lost in amniotes and nematodes, suggesting convergent evolution. We also observe that EXL-1 nuclear translocation occurs in a timely ordered manner in the intestine, from posterior to anterior regions. Finally, we find that exl-1 loss of function mutants are more susceptible to heat stress than wild-type animals, demonstrating functional relevance of the nuclear translocation. This research provides the first link between CLICs and environmental heat stress. We propose that C. elegans CLICs evolved to achieve different physiological functions through subcellular localization change and spatial separation in response to external or internal signals.